No dogs allowed! - Wallace, Bill, 1947- (New York : Holiday House, 2004)
Twelve-year-old Kristina, still struggling to come to terms with the death of her beloved horse, finds it difficult to accept the new dog she receives for her birthday.
Keywords: Dogs -- Fiction; Grief -- Fiction; Pets -- Fiction; Death -- Fiction; Friendship -- Fiction; Family life -- Fiction. --------------------------------------------------------------------------------